2023
DOI: 10.1155/2023/9484441
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Effective Oral Vaccine Dissemination Strategy against Classical Swine Fever for Wild Boar in Gifu Prefecture, Japan

Abstract: In September 2018, classical swine fever (CSF) reemerged in Japan after more than a quarter of a century. After the first notification on a pig farm, wild boars positive for CSF were found continuously in the surrounding area. Gifu was the first prefecture in Japan to disseminate oral vaccines to wild boars in March 2019, with vaccines spread to approximately 14,000 sites between 2019 and 2020. While these diligent measures seemed to have shown some effectiveness, several vaccine spray sites remained without w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…In the previous study, we performed a generalized linear mixed model (GLMM) analysis based on data from sensor cameras installed at approximately 10% of all vaccine dispersal points to identify areas where wild boar was most likely to appear. We found a positive correlation between the emergence of other wildlife (raccoon, raccoon dog, and crow) and the emergence of wild boar 20 . In addition, road density and vegetation were also estimated to influence wild boar emergence.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the previous study, we performed a generalized linear mixed model (GLMM) analysis based on data from sensor cameras installed at approximately 10% of all vaccine dispersal points to identify areas where wild boar was most likely to appear. We found a positive correlation between the emergence of other wildlife (raccoon, raccoon dog, and crow) and the emergence of wild boar 20 . In addition, road density and vegetation were also estimated to influence wild boar emergence.…”
Section: Introductionmentioning
confidence: 69%
“…The variable of vaccine dissemination season, a categorical variable, was subjected to a label encoding process. Our previous study found a correlation between the emergence of other animals and wild boar 20 , and therefore it may also influence the vaccine uptake rate of wild boar. The vaccine ingestion variable by other animals was treated as binary data for the same reasons as in the response variable setting.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…MAFF took a comprehensive approach, intensifying surveillance efforts in regions where CSF-affected wild boars were identified. In March 2019, an oral vaccine, commonly referred to as a bait vaccine, was strategically administered to wild boars in selected prefectures with positive CSF cases and in surrounding areas [ 30 ]. A study on CSF dynamics and wild boar bait vaccination in Japan found a 12.1 percentage point increase (95% CI: 7.8–16.5) in antibody prevalence from the 2019 vaccine campaigns.…”
Section: Strategiesmentioning
confidence: 99%
“…Here, we selected factors that could affect surveillance performance based on insights from previous wild boar research in Asia [22][23][24], Korean topographic features [25], and data availability. Five key factors were chosen: elevation, distance from the nearest roads, human PLOS ONE population density, percent tree cover (cover tree), and pig density.…”
Section: Estimation Of Under-surveilled Areasmentioning
confidence: 99%